M163. GLUTAMATE METABOLITES ARE ASSOCIATED WITH ALTERED HIPPOCAMPAL ACTIVATION BUT NOT HIPPOCAMPAL-STRIATAL CONNECTIVITY IN SUBJECTS WITH A CLINICAL HIGH RISK FOR PSYCHOSIS. (18th May 2020) - Hird, Emily; Allen, Paul; Orlov, Natasza; Modinos, Gemma; Bossong, Matthijs; Antoniades, Mathilde; Sampson, Carly; Azis, Matilda; Howes, Oliver; Stone, James; Grace, Antony; McGuire, Philip
Abstract: Background: We recently used Magnetic Resonance Spectroscopy (MRS) to show that transition to psychosis is associated with higher baseline hippocampal glutamate levels (1). We also used functional Magnetic Resonance Imaging (fMRI) in the same CHR subjects and showed that compared to healthy controls (HC), subjects at a clinical high-risk of psychosis (CHR) show decreased hippocampal activation to novel stimuli and increased novelty-modulated hippocampal-striatal connectivity (2). The aim of the present analysis was to explore the relationship between hippocampal glutamatergic metabolites, hippocampal activity, and hippocampal-striatal connectivity in these CHR subjects. Methods: 75 CHR and 31 HC subjects participated in a novelty salience task whilst undergoing fMRI to measure hippocampal and striatal activation, and MRS to measure hippocampal glutamatergic metabolite levels. First, we tested for a three-way interaction between the hippocampal response to novel versus neutral stimuli, hippocampal glutamatergic metabolite levels, and group, using a Region of Interest approach in the bilateral hippocampus. Second, we carried out a Psychophysiological Interaction (PPI) analysis on the extracted hippocampal coordinates from the first analysis and tested for an interaction with hippocampal glutamatergic metabolite levels and group. Results: The CHR group had higher clinical scores and lower GAF scores at baseline than HC. CHR subjects were younger, more were taking antipsychotic medication and they smoked more cigarettes than HC. At follow-up, 12 CHR subjects (16%) developed a first episode of psychosis (CHR-TR) and 63 (86%) did not (CHR-NTR). The CHR-TR subjects smoked fewer cigarettes than the CHR-NTR subjects. The first analysis revealed a significant interaction between group, fMRI activity and MRS Glx (a combined measure of glutamate and glutamine) in the right hippocampus (pFWE= 0.03; x y z = 28 -32 -4; t=3.61, z=3.49). This was driven by the CHR-TR group: contrast estimates indicated a positive relationship between fMRI activity and MRS Glx in the HC and CHR-NTR subjects, but a negative relationship between fMRI activity and glutamate in the CHR-TR subjects. The second analysis revealed that CHR-TR individuals exhibited greater connectivity between the hippocampus and the striatum (pFWE= 0.03; x y z = -6 6 -8; t=3.35, z=3.17), but that this was not associated with Glx. Discussion: Whilst hippocampal glutamate metabolite levels are associated with altered hippocampal activity in CHR individuals - especially in those who later transition to psychosis - hippocampal glutamate metabolite levels do not modulate connectivity between the hippocampus and striatum. These findings are broadly consistent with previous work indicating a role for glutamate in hippocampal dysfunction and risk for psychosis, and indicate a potential biomarker for psychosis risk. References: Bossong MG, Antoniades M, Azis M, Samson C, Quinn B, Bonoldi I, et al. (2018): Association of Hippocampal Glutamate Levels with Adverse Outcomes in Individuals at Clinical High Risk for Psychosis. JAMA Psychiatry. 1–9. Modinos G, Allen P, Zugman A, Dima D, Azis M, Samson C, et al. (2019): Neural Circuitry of Novelty Salience Processing in Psychosis Risk: Association with Clinical Outcome. 1–10.